Unwelcome Welcome – Being ‘at Home’ in an Age of Global Migration - Leif Dahlberg (Law Text Culture, 2014)
In this article I analyse contemporary conceptions of and attitudes to irregular immigrants in France as they are presented in national legislations and policy documents – generally as unwelcome, unwanted, undesired strangers. I also study how these laws and policies have been challenged by more hospitable and humane attitudes among activists, artists and culture producers as well as philosophers. In order to do this, I focus on a series of events and debates leading up to the most recent amendment of the French Code of Entry and Sojourn of Foreigners and of Right to Asylum (Code de l’entrée et du séjour des étrangers et du droit d’asile, abbreviated CESEDA). These events and debates highlight internal tensions and contradictions in contemporary conceptions of and attitudes to irregular migrants not only in France but in the European Union (EU) in general.